The Semiotics and social construction of Fat in Disney a thematic analysis of fat characters in selected live-action remakes of Disney princess films - Lanciola, Rhoda Janeia D.; Escano, Ma. Teresa R. (2023)
Disney is taking the route of recreating original animated films into live-action films, making for a curious site of analysis to determine where the company now stands in the march for positive inclusion of fat characters in their films. This thesis set out to investigate the portrayals of fat characters in the selected live-action remakes of Disney Princess films entitled ?Maleficent? (Stromberg, 2014), ?Cinderella? (Branagh, 2015), ?Beauty and the Beast? (Condon, 2017), ?Aladdin? (Ritchie, 2019), and ?Mulan? (Caro, 2020). The main aims of this study were to: (1) probe how fat characters were portrayed in these selected films and (2) determine if these portrayals of fat characters reinforce or challenge existing fat stereotypes in films. Utilizing the Semiotics Theory during the investigation of signs around and within these characters, followed by the Social Construction Perspective in the analysis of the findings and integrated with the existing study of Plotz (2020) in her mapping of common tropes of fatness in films, the study found that there were ten predominant ways a fat character is likely to be portrayed in the films: as a superior, weak, vulnerable, slow-witted, incompetent, motherly, non-normative feminine, uncontrolled, sidekick, and an eater. The results were found to be consistent with long-standing stereotypical roles of fat characters in films, with the exception that they are now in a toned down manner. It is still insufficient to say that stereotypical roles of fat people in films were challenged.
Thesis (BA Communication and Media Arts) --University of the Philippines Mindanao, 2023